A hierarchical approach for evaluating and selecting waste heat utilization opportunities. (October 2015) - Oluleye, Gbemi; Jobson, Megan; Smith, Robin
Abstract: This paper presents a ranking criterion for evaluating opportunities that utilize recovered energy from the available waste heat in process sites. The ranking criterion takes into account the energy performance of waste heat recovery technologies associated with each opportunity, their potential to reduce greenhouse gas emissions (namely CO2 ) and the economics (costs and benefits). Mathematical modelling of the opportunities using the ranking criterion is developed to allow for systematic evaluation of opportunities, for example within an optimization framework. A methodology using the ranking criterion to design site waste heat recovery systems is also proposed. The methodology is applied to a case study of a petroleum refinery. Hierarchy and performance of waste heat utilization opportunities depends on the temperature of the heat available, amongst other factors. The site operating cost and CO2 emissions reduce by 26% and 18% respectively when opportunities to use the recovered energy from waste heat within and outside the process site boundaries are explored. Sensitivity of the ranking to energy prices is studied, to explore the outlook for waste heat utilization in the future. The methodology can be applied to the process industries and other facilities producing waste heat. Highlights: Hierarchy introduced to opportunities using recovered energy from waste heat. Sensitivity analysis of ranking to changing inputs performed. Methodology developed to design waste heat recovery systems using the hierarchy. Analysis considers the temperature and duties of the available waste heat. Case study presented to illustrate application of the proposed methodology.